A 2-dimensional video based model for use in ergometer rowing kinematics - Warmenhoven, J.; Ball, N.; Draper, C.; Hunter, A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Motion capture of the rowing stroke using accurate 3D opto-reflective systems has been limited by the constraints of the surrounding hydrodynamic environment. As a consequence 2D lower-extremity kinematic models have been used in an attempt to counter these logistical issues (Lamb, 1989). Despite this, there is limited research supporting the accuracy of a 2D video based model (2DVBM) for motion capture of the rowing stroke. The purpose of this study was to assess the accuracy of a 2DVBM against the conventional gait model using a 3D opto-reflective system.